Pengaruh Tingkat Pendidikan, Pengangguran, dan Kemiskinan Terhadap Ketimpangan Pendapatan di Provinsi Sumatera Barat. - Yesi Badriatul Fadila; Idris (Universitas Negeri Padang, 2025)
This study aims to examine the influence of education level, unemployment, and poverty on income inequality in West Sumatra. The research utilizes secondary data with a quantitative approach through panel data regression methods, using data from the Central Bureau of Statistics (BPS). The variables analyzed include education level, unemployment, poverty, and income inequality. Based on the analysis results, the fixed effect model was selected. The estimation reveals that education level has a negative and significant effect on income inequality, unemployment has a positive but insignificant effect, while poverty has a positive and significant effect. Simultaneously, these three variables significantly influence income inequality in West Sumatra. The findings highlight the importance of improving education quality, providing job training programs, and creating new job opportunities as measures to reduce poverty and mitigate income inequality.